Effect of chronic administration of endothelin receptor type a antagonist (bq-610) on functional lifespan of the corpus luteum in sheep - Perea Ganchou, Fernando; Mankey, Julie Elizabeth; Puttaswamy Goravanahally, Madhusudan; Keith Inskeep, Emmett; Flores, Jorge Antonio (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Ver resumen pdf.